Unfired magnesia spinel brick and its manufacturing method

By adding basic alumina-lactic acid and aqueous sodium alumina solution to the fire-resistant material, and performing external coating treatment and extrusion molding, the difficulties in manufacturing high-thermal-resistant and high-thermal strength non-sintered magnesium-spinel bricks in the prior art are solved, and the dual goals of environmental protection and performance are achieved.

JP7650953B1Active Publication Date: 2025-03-25YOTAI REFRACTORIES
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023219900
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2025-03-25
Estimated Expiration
2043-12-26

Smart Images

  • Figure 0007650953000001
    Figure 0007650953000001
  • Figure 0007650953000002
    Figure 0007650953000002
Patent Text Reader

Abstract

The present invention provides an unfired magnesia spinel brick that contributes to reducing carbon dioxide emissions, has excellent heat spalling resistance and volume stability, and exhibits high hot strength, and a method for producing the same. [Solution] A method for producing unfired magnesia-spinel bricks, characterized by comprising the steps of: a first step of adding 1-2% by mass of an aqueous solution of sodium aluminate (outer percentage) to 100% of a refractory raw material containing magnesia and spinel as main components and 1-2% by mass of basic aluminum lactate, and kneading the mixture, and then obtaining a molded body of any shape; and a second step of drying the molded body obtained in the first step.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a refractory material which can be used, for example, as the lining of a furnace for burning cement, lime, etc. [Background technology]

[0002] Magnesia-spinel bricks have excellent heat-resistance against spalling and volumetric stability, and are primarily used in rotary kilns for burning cement and lime.

[0003] For example, Patent Document 1 (JP Patent Publication 08-026816A) has as its object "to provide a magnesia-spinel refractory suitable for lining bricks in rotary kilns for burning cement raw materials, lime raw materials, etc." and proposes "a magnesia-spinel refractory characterized by having 15-30% spinel clinker containing 3-10% ZrO2 and 50-80% electrofused magnesia clinker or seawater magnesia clinker of high purity and large crystal size."

[0004] In the magnesia spinel refractory described in the above Patent Document 1, in order to enable stable use even under high temperature operation, electrofused magnesia clinker having an MgO content of 98% and a large crystal grain size of 50 μm or more is used, and a spinel clinker containing 3 to 10% ZrO2 is used, which is said to have a sintering promotion effect and increase heat resistance.

[0005] Furthermore, in the durable magnesia-spinel cement and refractory for lime burning kilns described in Patent Document 2 (JP Patent Publication 07-061857A), the objective of which is to "provide a magnesia-spinel brick having improved wear resistance without impairing in any way the excellent spalling resistance that magnesia-spinel bricks possess," the document proposes "a magnesia-spinel refractory obtained by blending magnesia clinker and MgO-Al2O3 spinel clinker, in which 20% by weight or more of sintered magnesia clinker having a bulk specific gravity in the range of 3.20 to 3.37 is used as the magnesia clinker, and a highly durable cement and a magnesia-spinel burned brick for lime burning kilns."

[0006] In the durable magnesia-spinel cement and magnesia-spinel fired brick for lime burning kilns described in the above Patent Document 2, it is said that it is possible to increase hot strength to improve abrasion resistance without sacrificing other physical properties by simply using magnesia clinker with a specified bulk specific gravity. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 08-026816 [Patent Document 2] Japanese Patent Application Publication No. 07-061857 Summary of the Invention [Problem to be solved by the invention]

[0008] However, the magnesia-spinel refractory described in Patent Document 1 and the durable magnesia-spinel cement and refractory for lime burning kiln described in Patent Document 2 are both fired refractories manufactured through a firing process, and it is inevitable to emit a large amount of carbon dioxide during the manufacturing process.

[0009] On the other hand, from the viewpoint of carbon neutrality and curbing global warming in recent years, unfired refractories that do not require a firing process are superior. However, the reality is that there are currently no unfired magnesia-spinel bricks that are high in strength, excellent in heat spalling resistance and volume stability.

[0010] In view of the above-mentioned problems in the conventional techniques, an object of the present invention is to provide an unfired magnesia-spinel brick which contributes to a reduction in carbon dioxide emissions, has excellent heat spalling resistance and volume stability, and exhibits high hot strength, and to provide a method for producing the same. [Means for solving the problem]

[0011] In order to achieve the above object, the present inventors have conducted extensive research into unfired magnesia spinel bricks and a method for producing the same, and as a result, have discovered that it is extremely effective to incorporate basic aluminum lactate into the refractory raw material and to add an aqueous solution of sodium aluminate during kneading, thereby arriving at the present invention.

[0012] That is, the present invention provides: a first step of adding 1 to 2% by mass of an aqueous solution of sodium aluminate in an outer percentage to 100% of a refractory raw material containing magnesia and spinel as main components and 1 to 2% by mass of basic aluminum lactate, and kneading the mixture to obtain a molded body of any shape; A second step of drying the molded body obtained in the first step; The present invention provides a method for producing an unfired magnesia spinel brick, comprising the steps of:

[0013] In the past, no unfired magnesia spinel bricks that have not undergone a firing process have been found that exhibit high hot strength in addition to high strength, excellent heat spalling resistance and volume stability. In contrast, the unfired magnesia spinel bricks of the present invention can be endowed with all of these properties by mixing appropriate amounts of basic aluminum lactate and an aqueous solution of sodium aluminate.

[0014] More specifically, by mixing an appropriate amount of basic aluminum lactate and sodium aluminate, gelation occurs and aluminum lactate is produced. Since aluminum lactate has a moisturizing effect, the drying of the clay is suppressed, and a good molded body can be obtained (first step).

[0015] Furthermore, when the obtained molded body is dried at an appropriate temperature, lactate salts such as sodium lactate remain without being decomposed, making it possible to suppress a decrease in strength (second step).

[0016] In the method for producing an unfired magnesia spinel brick of the present invention, it is preferable that the Al2O3 solid content concentration of the aqueous sodium aluminate solution is 10 to 20 mass %.

[0017] By adding an aqueous sodium aluminate solution with an Al2O3 solids concentration of 10 to 20 mass% in an outer percentage of 1 to 2 mass% to 100% refractory raw material containing basic aluminum lactate, lactate salts such as sodium lactate decompose during the heating process when used in an actual furnace, and lactic acid evaporates, allowing the highly active aluminum to react with magnesia, allowing the reaction between aluminum and magnesia to form a spinel, which can proceed sufficiently and smoothly.

[0018] Furthermore, in the method for producing an unfired magnesia spinel brick of the present invention, it is preferable that the drying temperature in the second step is set to 200 to 320° C. By setting the drying temperature to 200° C. or higher, the decomposition of sodium lactate and lactic acid can be suppressed while the drying can proceed sufficiently and smoothly, and by setting the drying temperature to 320° C. or lower, a decrease in the strength of the unfired magnesia spinel brick can be suppressed and an increase in carbon dioxide emissions related to the drying step can be suppressed.

[0019] The present invention also provides a method for producing a semiconductor device comprising the steps of: Contains 0.5 to 1.5 mass% lactate ions, The bending strength at 1200℃ is 5MPa or more. The present invention also provides an unfired magnesia spinel brick, characterized by:

[0020] The unfired magnesia spinel brick of the present invention is obtained by the method for producing an unfired magnesia spinel brick of the present invention, and contains 0.5 to 1.5 mass % of lactate ions by carrying out a first step of adding 1 to 2 mass % of an aqueous sodium aluminate solution by outer percentage to 100% of a refractory raw material containing magnesia and spinel as main components and 1 to 2 mass % of basic aluminum lactate, and kneading the mixture, and then obtaining a molded body of any shape, and a second step of drying the molded body obtained in the first step.

[0021] Moreover, the unfired magnesia brick of the present invention has high hot strength, with a bending strength of 5 MPa or more at 1200°C. A dense molded body can be obtained by the method for producing an unfired magnesia brick of the present invention, and lactate salts such as sodium lactate remain without decomposition when the molded body is dried at an appropriate temperature. As a result, lactate salts such as sodium lactate decompose and lactic acid evaporates during the heating process up to 1200°C, and highly active aluminum reacts with magnesia, allowing the reaction between aluminum and magnesia to form a spinel sufficiently and smoothly, thereby enabling the brick to exhibit high hot strength. Effect of the Invention

[0022] INDUSTRIAL APPLICABILITY The present invention provides an unfired magnesia spinel brick having excellent heat spalling resistance and volume stability and exhibiting high hot strength, which contributes to reducing carbon dioxide emissions, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Representative embodiments of the unfired magnesia-spinel brick and the method for producing the same according to the present invention will be described in detail below, but the present invention is not limited to these.

[0024] 1. Manufacturing method of unfired magnesia spinel bricks The method for producing the unfired magnesia-spinel brick of the present invention comprises the steps of: a first step of adding 1-2% by mass of an aqueous solution of sodium aluminate by outer percentage to 100% of a refractory raw material containing magnesia and spinel as main components and 1-2% by mass of basic aluminum lactate; kneading the mixture; and obtaining a molded body of any shape; and a second step of drying the molded body obtained in the first step. Each step will be described in detail below.

[0025] (1) First step The first step is a step for obtaining a molded body of any shape by adding 1 to 2 mass% of an aqueous solution of sodium aluminate to 100% of a refractory raw material containing magnesia and spinel as main components and 1 to 2 mass% of basic aluminum lactate, and kneading the mixture.

[0026] (1-1) Main component The refractory raw material as the main component may be magnesia particles and spinel particles. The mixing ratio of the magnesia particles and the spinel particles is not particularly limited as long as the effect of the present invention is not impaired, and may be appropriately adjusted according to the desired properties of the unfired magnesia-spinel brick.

[0027] The magnesia particles and spinel particles are preferably mixed from raw materials having different particle sizes, which can impart good heat spalling resistance to the unfired magnesia-spinel brick.

[0028] The type of magnesia raw material is not particularly limited as long as it does not impair the effects of the present invention, but for example, conventionally known electrofused magnesia, seawater magnesia, natural magnesia, etc. In addition, regarding the purity of the magnesia raw material, it is preferable to use a high purity of 95% by weight or more in order to avoid the deterioration of corrosion resistance due to impurities and the influence of over-sintering.

[0029] The type of spinel raw material and the ratio of MgO to Al2O3 are not particularly limited as long as they do not impair the effects of the present invention, and for example, a conventionally known alumina-magnesia spinel (MgAl2O4) can be used. As with the magnesia raw material, it is preferable to use a spinel raw material with a high purity of 95% by weight or more. The spinel raw material is not particularly limited, and electrically fused spinel, fired spinel, etc. can be used.

[0030] (1-2) Essential additives (binders) As an essential additive component, 1 to 2 mass% of basic aluminum lactate is added. Also, 1 to 2 mass% of sodium aluminate aqueous solution is added in an outer percentage to 100% of the refractory raw material containing magnesia and spinel as main components and 1 to 2 mass% of basic aluminum lactate.

[0031] The Al2O3 solid content concentration of the sodium aluminate aqueous solution is preferably 10 to 20 mass%, more preferably 14 to 18 mass%. By adding an aqueous sodium aluminate solution having an Al2O3 solid content concentration of 10 to 20 mass% (outer percentage: 1 to 2 mass%) to 100% of the refractory raw material containing 1 to 2 mass% basic aluminum lactate, the reaction between aluminum and magnesia to form a spinel can be sufficiently and smoothly promoted.

[0032] (1-3) Optional additives For example, 1 to 3 mass% of sorbitol can be added as a molding aid to 100% of the refractory raw material. Sorbitol is composed mainly of D-sorbitol and is represented by HOCH2(CHOH)4CH2OH. It is a powder that dissolves easily in water and is generally used as a surfactant or food additive. The addition of sorbitol improves the filling property of the kneaded clay and the lubrication between particles, reduces the change of the clay over time, and suppresses slaking. It is also non-toxic and can obtain a molded body with a high molding density. Additives that are used as molding aids for fired spinel bricks, such as bittern and magnesium sulfate, can also be used.

[0033] In addition, various conventionally known optional components such as alumina, zirconia, and iron oxide may be added to magnesia-spinel bricks as long as the effects of the present invention are not impaired.

[0034] (1-4) Mixing and molding The refractory raw material as the main component, the essential additive components, and the optional additive components are kneaded and formed into a desired shape. The kneading and forming methods are not particularly limited, and various conventional methods used in the manufacture of refractories can be applied.

[0035] In the method for producing an unfired magnesia spinel brick of the present invention, appropriate amounts of sodium aluminate and basic aluminum lactate are mixed together to cause gelation and generate aluminum lactate. Since aluminum lactate has a moisturizing effect, the drying of the clay is suppressed, and a good molded body can be obtained.

[0036] (2)Second process The second step is a step for drying the molded body obtained in the first step to obtain an unfired magnesia-spinel brick.

[0037] If the molded body obtained in the first step is dried at an appropriate temperature, lactate salts such as sodium lactate remain without being decomposed, and a decrease in strength can be suppressed.

[0038] The drying temperature is preferably 200 to 320°C. By setting the drying temperature at 200°C or higher, excess water is evaporated and dehydrated, thereby increasing strength. Furthermore, by setting the drying temperature at 320°C or lower, lactate salts such as sodium lactate remain without being decomposed, and a decrease in strength can be suppressed, and an increase in carbon dioxide emissions associated with the drying process can be suppressed. The drying temperature is more preferably 250 to 300°C.

[0039] The method for drying the molded body is not particularly limited, and various conventionally known methods used in the production of unfired refractories can be applied.

[0040] The method for producing an unfired magnesia spinel brick of the present invention does not prevent the dried unfired magnesia spinel brick from being fired under appropriate conditions.

[0041] 2. Unfired magnesia spinel bricks The unfired magnesia spinel brick of the present invention is characterized by containing 0.5 to 1.5 mass % of lactate ions and having a bending strength at 1200°C of 5 MPa or more.

[0042] The method for measuring the content of lactate ions in the unfired magnesia spinel brick is not particularly limited, and various conventionally known measuring methods can be used, for example, lactate ions can be quantified by thermogravimetric analysis. More specifically, a simultaneous differential thermal-thermogravimetric analyzer is used to heat the unfired magnesia spinel brick under an air flow, and the weight change at 350 to 400°C, which is the decomposition and evaporation temperature of lactic acid derived from aluminum lactate and sodium lactate, is measured.

[0043] The method for measuring the bending strength of the unfired magnesia spinel brick at 1200°C is not particularly limited, and various conventionally known measuring methods can be used. For example, a three-point bending test can be performed in an air atmosphere at 1200°C using a hot bending tester. The bending strength of the unfired magnesia spinel brick at 1200°C is preferably 7 MPa or more, and more preferably 9 MPa or more.

[0044] Furthermore, the unfired magnesia spinel brick of the present invention has sufficient strength even at room temperature, and has a higher compressive strength than a fired magnesia spinel brick having the same composition but not containing lactate ions.

[0045] Furthermore, the unfired magnesia spinel brick of the present invention has excellent corrosion resistance, hot spalling resistance and microstructural embrittlement resistance, which are comparable to those of a fired magnesia spinel brick having the same composition but not containing lactate ions.

[0046] Representative embodiments of the present invention have been described above, but the present invention is not limited to these, and various design modifications are possible, all of which are included in the technical scope of the present invention. EXAMPLES

[0047] Example The raw materials were prepared in the proportions shown in Table 1 as Examples 1 to 6, kneaded in a high-speed mixer, and molded into a shape of 230 x 230 x 85 mm using a hydraulic press. A batch-type dryer was used for drying, and the mixture was kept at 200 to 320°C for 8 hours to obtain unfired magnesia-spinel bricks, which are examples of the present invention. The values ​​in Table 1 are shown in mass%, and the amounts of the aqueous sodium aluminate solution, the aqueous sorbitol solution, and the water added are shown as values ​​multiplied by the total amount of the magnesia clinker, the spinel clinker, and the basic aluminum lactate. In addition, the particle size of the magnesia clinker and the spinel clinker and the Al2O3 solid concentration (mass%) of the aqueous sodium aluminate solution are shown.

[0048] Comparative Example Unfired magnesia spinel bricks were obtained in the same manner as in the Examples, except that the raw materials were adjusted in the proportions shown in Comparative Examples 1 to 8 in Table 1. Here, only Comparative Example 1 was fired in a tunnel kiln at a maximum temperature of 1750±10°C.

[0049] [Table 1]

[0050] [evaluation] The unfired magnesia-spinel bricks obtained as the examples and comparative examples were evaluated for corrosion resistance, compressive strength, hot strength, heat spalling resistance, and microstructural embrittlement resistance. In addition, the lactate ion content of each unfired magnesia brick was measured.

[0051] (1) Corrosion resistance The corrosion resistance was evaluated by a rotating drum corrosion test. The test method is as follows. The test piece was lined inside the drum, and the test was performed at 1750±50°C using an oxygen-propane burner. A mixture of Portland cement and potassium sulfate in a ratio of 5:1 was added as the corrosion material. After the test was held for 6 hours while changing the corrosion material every hour, the sample was cut in a direction perpendicular to the working surface, and the amount of wear was measured at 8 points to obtain the average amount of wear. The average amount of wear was expressed as an index with the amount of wear in Comparative Example 1 set to 100. The results are shown in Table 2. The smaller the index, the better the corrosion resistance. When the index was 105 or less, it was marked as ◯, when it was more than 105 but less than 110, it was marked as △, and when it was 110 or more, it was marked as ×.

[0052] (2) Compressive strength The compressive strength of the 60 mm x 60 mm x 60 mm test pieces was measured using an Amsler strength tester. The compressive strength was evaluated using an index based on the fired magnesia spinel brick of Comparative Example 1, which is a fired product, being 100. The results are shown in Table 2.

[0053] (3) Hot strength Hot strength was measured on a 30mm x 30mm x 120mm test piece using a hot bending test device. The results of three-point bending (support distance 80mm) in an air atmosphere at 1200°C are shown as numerical values ​​(MPa). The results are shown in Table 2. The higher the numerical value, the higher the hot strength, with less than 5 being marked x, between 5 and 7 being marked △, and 7 or more being marked ◯.

[0054] (4) Heat spalling resistance Heat spalling resistance was evaluated using the air cooling method based on JIS R2657. The temperature condition was 1400°C, and heating and cooling were performed a maximum of 10 times. If the specimen spalled during the process, the number of operations at which it spalled was recorded, and if it did not spall until the end, the depth of the crack was measured. The depths of the cracks were compared relatively, and large cracks were rated "large", medium cracks were rated "medium", and small cracks were rated "small". The results are shown in Table 2.

[0055] (5) Resistance to structural embrittlement After the heat spalling resistance test, the test piece was cut perpendicular to the working surface, and the surface condition of the cut surface was confirmed. The depth of grain shedding from the heated surface was taken as the embrittled layer, and the resistance to embrittlement was evaluated. A grain shedding range of 60 or less was rated as ◯, a range between 60 and 80 was △, and a range over 80 was ×. The results are shown in Table 2.

[0056] (6) Lactate ion content The amount of lactate ions was quantified by thermogravimetric analysis. The measurement device for differential thermal and thermogravimetric simultaneous analysis was STA7300 manufactured by Hitachi High-Tech Science Corporation. The sample (unfired magnesia spinel brick) was weighed on the balance beam of the STA7300. Approximately 10 mg of the sample was placed in a platinum measurement container and set in the above measurement device, and the temperature was raised from 20 to 1000 °C at a rate of 5 °C / min under an air flow of 200 ml / min to obtain a DTG curve. The content of lactate ions contained in the unfired magnesia spinel brick was calculated based on the weight loss peak at 350 to 400 °C due to the decomposition and evaporation of lactic acid derived from aluminum lactate and sodium lactate. The results are shown in Table 2.

[0057] [Table 2]

[0058] In the examples of the present invention, all the unfired magnesia spinel bricks have a lactate ion content of 0.5 to 1.5 mass %. All the unfired magnesia spinel bricks exhibit high hot strength, with a hot bending strength of 5 MPa or more at 1200°C. In contrast, in the comparative examples, there are no unfired magnesia spinel bricks that contain 0.5 to 1.5 mass % lactate ions and have a hot bending strength of 5 MPa or more at 1200°C.

[0059] In addition, in the examples of the present invention, the unfired magnesia spinel bricks of all the examples were evaluated as ◯ in corrosion resistance and heat spalling resistance. In Example 4, in which a sorbitol aqueous solution was used instead of water, the embrittlement range increased slightly, but the structural embrittlement resistance of all the unfired magnesia spinel bricks of the examples was evaluated as △ or higher. In addition, the hot bending strength of all the unfired magnesia spinel bricks of the examples was evaluated as △ or higher. In particular, the hot bending strength of Example 3 was evaluated as ◯, and good results were obtained in all evaluation items. As a result, it is found that the unfired magnesia spinel brick of Example 3 has properties equivalent to those of the fired magnesia spinel brick of Comparative Example 1.

[0060] In contrast, in Comparative Example 2, in which the amount of basic aluminum lactate added was too small, the bonding phase was not sufficiently present, so the hot bending strength was low, and the heat spalling resistance and microstructural embrittlement resistance were also evaluated as X. Moreover, in Comparative Example 3, in which the amount of basic aluminum lactate added was too large, the corrosion resistance was evaluated as X because a large amount of lactic acid that does not contribute to spinel bonding was included.

[0061] In Comparative Example 4, in which the Al2O3 solid content concentration of the sodium aluminate aqueous solution was too low, the bonding phase was not sufficiently present, and the hot bending strength was low.In Comparative Example 5, in which the Al2O3 solid content concentration of the sodium aluminate aqueous solution was too high, drying occurred quickly during molding, making it difficult to obtain sufficient strength for the molded body, and the hot bending strength was low.

[0062] In Comparative Example 6, in which the amount of sodium aluminate solution added was too large, the soda content was too high, and as a result, the corrosion resistance and resistance to structural embrittlement were evaluated as ×.

[0063] Moreover, in Comparative Example 7 in which the drying temperature was too low, and in Comparative Example 8 in which the drying temperature was too high, the compressive strength was low.

[0064] From the above results, it is clear that in order to obtain unfired magnesia-spinel bricks with high strength and excellent heat spalling resistance and volume stability, it is important to add 1 to 2 mass% of an aqueous solution of sodium aluminate on an outer basis to 100% refractory raw material containing magnesia and spinel as main components and 1 to 2 mass% of basic aluminum lactate.

Claims

[Claim 1] a first step of adding 1 to 2% by mass of an aqueous solution of sodium aluminate in an outer percentage to 100% of a refractory raw material containing magnesia and spinel as main components and 1 to 2% by mass of basic aluminum lactate, and kneading the mixture to obtain a molded body of any shape; A second step of drying the molded body obtained in the first step, The sodium aluminate aqueous solution has an Al 2 O 3 solid content concentration of 10 to 20 mass %, The drying temperature in the second step is 200 to 320° C.; A method for producing unfired magnesia spinel bricks, comprising the steps of:

Citation Information

Patent Citations

  • Refractory composition

    JP1987158158A

  • Magnesia spinel cement having high durability and refractory for lime-burning kiln

    JP1995061857A

  • Spinel-based unburned refractory

    JP1995101780A

  • Magnesia spinel-based refractory

    JP1996026816A

  • Production of magnesia-chromium-based refractory product

    JP1999157917A